Clinical characteristics and penile afferent neuronal function in patients with primary delayed ejaculation. (22nd August 2013) - Xia, J.‐D.; Han, Y.‐F.; Pan, F.; Zhou, L.‐H.; Chen, Y.; Dai, Y.‐T.
Summary: Primary delayed ejaculation (DE) is a relatively uncommon condition and has not been studied broadly. In this study, we aimed to investigate the clinical characteristics and penile afferent neuronal function using somatosensory evoked potentials in patients with primary DE. Twenty‐four patients with primary DE and 24 age‐matched normally potent men were enrolled in this study. Results indicated that patients with primary DE had remarkably higher frequency of masturbatory activity (especially, some with idiosyncratic styles), lower night emissions, longer intravaginal ejaculation latency time (IELT), higher anxiety and depression states ( p = 0.010, p = 0.017, p < 0.001, p < 0.001, p < 0.001 respectively). In addition, the mean penile shaft sensory threshold values in the patients were considerably higher than those in the healthy men ( p < 0.001). Mean latencies of dorsal nerve somatosensory evoked potential DNSEP were 4.32 ms longer in the DE group than those in the control group ( p < 0.001). However, the latencies of glans penis somatosensory evoked potential (GPSEP) between the two group showed no significant difference ( p = 0.985). At the same time, in comparison with the control group, the amplitudes of DNSEP were considerably lower in the DE group ( p = 0.016), but not in the amplitudes of GPSEP ( p = 0.934). This study indicates that the patients with primary DE appear to have penile shaft rather than glans hyposensitivity and hypoexcitability, and adaptation to a certain masturbatory technique (higher and idiosyncratic) may be related to the causes of primary DE, which is also associated with lower night emissions, longer IELT, higher anxiety and depression states.